IMPLEMENTASI TEKNOLOGI INFORMASI BERBASIS WEB PADA UNIT PENGUMPUL ZAKAT UNTUK MENINGKATKAN EFEKTIVITAS DAN EFISIENSI PENGUMPULAN ZAKAT - Rendi Andriana Miftahul Rozab; Siti Nur; Muhamad Iqbal Felayati (STKIP PGRI Situbondo, 2023)
The implementation of information technology on a website is one way to improve the effectiveness and efficiency of zakat distribution in the Zakat Collecting Unit of Yayasan Keluarga Besar Cikeuleupu. The SDLC method is used as a reference for system design, starting with planning, analysis, design, development, testing, and development as the final stage of the design. All information related to zakat is taken from several sources, including the decision of the Ijtima' Ulama Commission on Fatwa VII, the yellow book Sullam Taufiq, and the results of the First International Zakat Conference in Kuwait (29 Rajab 1404). Zakat is not only an act of worship whose benefits are felt by individuals, but also a social act that provides benefits to the wider community. With zakat, social inequality between the poor and the rich can be reduced.